Isolation and characterization of DNA aptamers against the HlyE antigen of Salmonella Typhi - Mohamad Ahmad Najib; Anja Winter; Khairul Mohd Fadzli Mustaffa; Eugene Boon Beng Ong; Kasturi Selvam; Muhammad Fazli Khalid; Mohd Syafiq Awang; Asrulnizam Abd Manaf; Yazmin Bustami; Ismail Aziah (Scientific Reports)
Abstract Aptamers have emerged as prominent ligands in clinical diagnostics because they provide various advantages over antibodies, such as quicker generation time, reduced manufacturing costs, minimal batch-to-batch variability, greater modifiability, and improved thermal stability. In the present study, we isolated and characterized DNA aptamers that can specifically bind to the hemolysin E (HlyE) antigen of Salmonella Typhi for future development of typhoid diagnostic tests. The DNA aptamers against Salmonella Typhi HlyE were isolated using systematic evolution of ligands by exponential enrichment (SELEX), and their binding affinity and specificity were assessed utilizing enzyme-linked oligonucleotide assay (ELONA). A total of 11 distinct aptamers were identified, and the binding affinities and species selectivities of the three most probable aptamers were determined. Kd values were obtained in the nanomolar range, with the highest affinity of 83.6 nM determined for AptHlyE97. In addition, AptHlyE11, AptHlyE45 and AptHlyE97 clearly distinguished S. Typhi HlyE from other tested bacteria, such as Salmonella Paratyphi A, Salmonella Paratyphi B, Shigella flexneri, Klebsiella pneumonia and Escherichia coli, therefore displaying desirable specificity. These novel aptamers could be used as diagnostic ligands for the future development of inexpensive and effective point-of-care tests for typhoid surveillance, especially in developing countries of the tropics and subtropics.